VACUUM-ASSISTED BREAST BIOPSYIN THE DIAGNOSIS AND MINIMALLY INVASIVE TREATMENT INTRADUCTAL PAPILLOMAS OF THE BREAST - Левченко, Кирилл Федорович; Баранов, Андрей Игоревич (Medicine in Kuzbass, 2018)
The article describes the application of the method of vacuum-assistedbreastbiopsy (VAB) in intraductal papillomas of the breast for diagnostic and therapeutic purposes. Diagnosis of intraductal papillomas ambiguous and raises many questions and discussions. The therapeutic aspect of VAB application raises even more questions among specialists from different countries. However, VAB has undeniable advantages in the diagnosis and treatment of introducal changes of the breasts. VAB is gradually replacing the overly radical approaches in the treatment of various diseases of breasts and intraductal changes are no exception.